Penyusunan Laporan Keuangan Berdasarkan Standar Akuntansi Keuangan: Tantangan dan Hambatan - Sari, Khasnita; Nasution, Yenni Samri Juliati; Syafina, Laylan (Jurusan Akuntansi Politeknik Negeri Malang, 2024)
Abstract: Preparation of Financial Statements Based on Financial Accounting Standards: Challenges and Obstacles.Purpose: This study aims to determine the conformity between financial accounting standards and the preparation of financial reports that are carried out by the office of the Ministry of Religion of Bener Festive Aceh district. Method: This study uses the qualitative descriptive method with a case study approach.Results: The District Ministry of Religion Office prepares financial reports. Indeed, Meriah, Aceh largely follows financial accounting standards. The Ministry of Religion Office has prepared financial reports consisting of a Balance Sheet, Capital Changes Report, and Cash Flow Report.Novelty: This research presents challenges and obstacles in preparing and recording financial reporting based on financial accounting standards to create stable financial report preparation for a government entity.Contribution: This paper contributes to give solutions to prepare stable financial reports based on financial accounting standards. Abstrak: Penyusunan Laporan Keuangan Berdasarkan Standar Akuntansi Keuangan: Tantangan dan Hambatan.Tujuan: Penelitian ini bertujuan untuk mengetahui kesesuaian antara standar akuntansi keuangan dengan penyusunan laporan keuangan yang dilakukan oleh kantor kementerian agama kabupaten Bener Meriah Aceh.Metode: Penelitian ini menggunakan metode deskriptif kualitatif dengan pendekatan studi kasus.Hasil: Penyusunan laporan keuangan yang dilakukan oleh Kantor Kemenag Kabupaten Bener Meriah, Aceh sebagian besar sudah sesuai dengan Standar Akuntansi Keuangan. Kantor Kemenag ini sudah membuat laporan keuangan yang terdiri dari Neraca, Laporan Perubahan Modal, dan Laporan Arus Kas.Kebaruan: Penelitian ini menyajikan tantangan dan hanbatan penyusunan laporan keuangan berdasarkan standar akuntansi keuangan untuk menciptakan penyusunan laporan keuangan yang stabil untuk entitas pemerintahan.Kontribusi: Penelitian ini berkontribusi untuk memberikan solusi penyusunan laporan keuangan yang stabil berbasis Standar Akuntansi Keuangan.